2007
DOI: 10.30972/bon.160158
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomía del género <i>Arachis</i> (Leguminosae)

Abstract: Pasaron casi 100 a&ntilde;os entre la designaci&oacute;n por Linneo de la entonces &uacute;nica especie de&nbsp;<em>Arachis&nbsp;</em>(<em>A. hypogaea&nbsp;</em>L.) conocida por los europeos, y el primer tratamiento taxon&oacute;mico del g&eacute;nero por Bentham en 1841. Durante los siguientes 100 a&ntilde;os, aparecieron cinco a diez descripciones de especies adicionales, que asignaban diferentes especies a los mismos nombres, y diferentes nombres a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
381
0
32

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 271 publications
(427 citation statements)
references
References 0 publications
14
381
0
32
Order By: Relevance
“…The complete homology observed here in the insertion and deletion sequences that manifested A. monticola and A. hypogaea tetraploid taxa very near and similar genome composition. The current finding also justifies the high rate of crossability and achieving fertile progenies reported by Krapovickas and Gregory (1994). Albeit, the dendrogram of tetraploid species, showed that A. monticola grouped separately from the other botanical types, which affirms the belief that it is a separate species from A. hypogaea .…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…The complete homology observed here in the insertion and deletion sequences that manifested A. monticola and A. hypogaea tetraploid taxa very near and similar genome composition. The current finding also justifies the high rate of crossability and achieving fertile progenies reported by Krapovickas and Gregory (1994). Albeit, the dendrogram of tetraploid species, showed that A. monticola grouped separately from the other botanical types, which affirms the belief that it is a separate species from A. hypogaea .…”
Section: Discussionsupporting
confidence: 87%
“…Arachis species is considered to be the most diverse, holding both annual and perennial species and distinct chromosome numbers, karyotype structures and ploidy levels as it was a group apart but very close to Erectoides and Procumbentes Krapovickas and Gregory, 1994). On the other hand, Heteranthae and Caulorrhizae grouped together indicating that some species of the sections Heteranthae and Caulorrhizae may be capable of producing hybrids with Arachis section while a substantial genetic isolation persists with the other sections (Bertioli et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations